Essential oils in the control of Colletotrichum gloeosporioides f. Sp. cepae in onion seeds - Lozada, Maria Isabel; Silva, Patricia; Pereira, Ricardo; Nascimento, Warley (Revista Ciência Agronômica, 2019)
Anthracnose, one of the major diseases in the onion, is caused by the fungus Colletotrichum gloeosporioides f. sp. cepae. The main strategy for controlling this fungus is by the use of fungicide, with this technique being used on the majority of crops. Currently, methods of disease control are being studied that are less aggressive to the environment, with the use of essential oils proving to be an alternative. As such, the aim of this study was to evaluate the direct effect of the essential oils of basil (Ocimum basilicum), lemongrass (Cymbopogon citratus (DC) Stapf.), sage (Salvia officinalis), thyme (Thymus vulgaris) and citronella (Cymbopogon winterianus) as an alternative in the control of the fungus C. gloeosporioides f. sp. cepae, in addition to determining its effect on the physiological quality of onion seeds. The essential oils of lemongrass and sage did not affect the physiological quality of the onion seeds, and all the essential oils used helped to inhibit spore germination in C. gloeosporioides f. sp. cepae. The essential oils of thyme, lemongrass and citronella at a concentration of 2000 ppm completely inhibited mycelial growth in the fungus. Treatment with the essential oil of lemongrass in seeds inoculated with the pathogen gave greater protection against fungal attack.